Association between triglyceride-glucose (TyG) index and risk of depression in middle-aged and elderly Chinese adults: Evidence from a large national cohort study - Zhang-Yang Xu; Hong Zheng; Zi-Jun Pan; Shou-Yi Hu; Yun-Xia Wang; Wen-Jun Su (Biomolecules & Biomedicine)
Insulin resistance has been proposed as a contributing factor to major depressive disorder (MDD), with previous studies reporting a positive correlation between triglyceride-glucose (TyG) a proxy indicator of insulin resistance and MDD. However, limited information is available regarding their longitudinal association. This study aimed to clarify the connection between TyG levels and depression risk, as well as explore its predictive potential. A total of 3,021 participants without a prior history of depression were recruited from the China Health and Retirement Longitudinal Study (CHARLS) and followed for seven years. Participants were categorized into tertiles based on their TyG levels. The cumulative hazard of depression was analyzed using Kaplan-Meier curves, while Cox regression analyses and multivariable-adjusted restricted cubic spline (RCS) curves were employed to assess the relationship between TyG levels and depression risk. Stratified analyses across various subgroups were also conducted to confirm the robustness of the conclusions.Over the follow-up period, 1,782 participants (58.9%) developed depression, with incidence rates of 30.2%, 34.0%, and 35.8% in tertiles 1, 2, and 3, respectively. After adjusting for confounding factors, each 1-unit increase in TyG was associated with a significantly higher risk of depression. RCS curve analysis revealed a compelling dose-response relationship between TyG levels and depression susceptibility. These findings indicate that elevated TyG levels are strongly associated with an increased risk of depression and could serve as a reliable biomarker for assessing depression risk. These insights provide valuable guidance for developing more effective strategies for the prevention and treatment of depressive disorders.